An-Naht dalam Bahasa Indonesia dan Bahasa Arab (Kajian Analisis Kontrastif) (JURNAL MAHASANTRI, 2020)
The Arabic and the Indonesian language each of them have the different language systems. Both of this language have the theory of an-naht which is influence the development of both systems. The case of an-naht in Arabic and Indonesian language becomes the subject that has been eliminated from the scope of linguistic. So that this study is almost inaudible among Arabic learners. Therefore, the writer wants to reconstruct to see the language from all sides, both in a microlinguistically or in a macrolinguistically. The contrastive analysis is an analysis which is compare two languages with accurate data to find similarities and differences between the two languages studied. The definition of an-naht in Arabic language is a theory that formulates two or more words into a new expression that shows its original meaning. According to Imil Badi’ Ya’qub, an-naht in Arabic language is classified into four kinds: 1) an-Naht an-Nisbiy, 2) an-Naht al-Fi’liy, 3) an-Naht al-Ismiy, 4) an-Naht al-Washfiy.As for the definition of acronym in Indonesian language is an abbreviation which is a combination of initial letters, syllable combinations, or a combination of letters and syllables from the word series that are required as a word.The acronym in Indonesian language divided into three: 1)Self-name acronym which is a combination of the initial letters of a word series written entirely with capital letters, 2) Self-name acronym which is a combination of the syllables or a combination of the letters and the syllables from a word series are written with capital letters first, 3) Acronym that is not personal name which is a combination of the letters, syllables or a combination of the letters and syllables from a word series written entirely with lowercase. The findings obtained that one of the difference between an-naht in the two languages can be seen from the division of an-naht itself. In that division it is very clear that the formation of an-naht in Arabic language can bring up into four variations, whereas in Indonesian language there are only three variations of its formation. The another difference, an-naht that appears in Arabic grammatic is claimed to destroy the purity of Arabic language by some Arabic linguists, but some other Arabic linguists allow the existence of an-naht if in the sience of isytiqaq it is found that there are difficulties that occur in the complex problem of lexical structure and Arabic grammatic, so it is necessary to bring up the theory of an-naht. While in the Indonesian language, An-naht precisely it contributes to the development of the Indonesian language itself, so that the Indonesian language remains dynamic and can answer global challenges.